New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves—they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains—including those in child welfare, economic support, criminal justice, education, and health care systems—and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.
Keywords: Behavioral and Social Sciences; Health and Medicine

Capturing Social and Behavioral Domains in Electronic Health Records: Phase 1 - Institute of Medicine (The National Academies Press, 2014)
Substantial empirical evidence of the contribution of social and behavioral factors to functional status and the onset and progression of disease has accumulated over the past few decades. Electronic health records (EHRs) provide crucial information to providers treating individual patients, to health systems, including public health officials, about the health of populations, and to researchers about the determinants of health and the effectiveness of treatment. Inclusion of social and behavioral health domains in EHRs is vital to all three uses. The Health Information Technology for Economic and Clinical Health Act and the Patient Protection and Affordable Care Act place new importance on the widespread adoption and meaningful use of EHRs. "Meaningful use" in a health information technology context refers to the use of EHRs and related technology within a health care organization to achieve specified objectives. Achieving meaningful use also helps determine whether an organization can receive payments from the Medicare EHR Incentive Program or the Medicaid EHR Incentive Program. Capturing Social and Behavioral Domains in Electronic Health Records is the first phase of a two-phase study to identify domains and measures that capture the social determinants of health to inform the development of recommendations for meaningful use of EHRs. This report identifies specific domains to be considered by the Office of the National Coordinator, specifies criteria that should be used in deciding which domains should be included, identifies core social and behavioral domains to be included in all EHRs, and identifies any domains that should be included for specific populations or settings defined by age, socioeconomic status, race/ethnicity, disease, or other characteristics.
Keywords: Health and Medicine

Capturing Change in Science, Technology, and Innovation: Improving Indicators to Inform Policy - National Research Council (The National Academies Press, 2014)
Since the 1950s, under congressional mandate, the U.S. National Science Foundation (NSF) - through its National Center for Science and Engineering Statistics (NCSES) and predecessor agencies - has produced regularly updated measures of research and development expenditures, employment and training in science and engineering, and other indicators of the state of U.S. science and technology. A more recent focus has been on measuring innovation in the corporate sector. NCSES collects its own data on science, technology, and innovation (STI) activities and also incorporates data from other agencies to produce indicators that are used for monitoring purposes - including comparisons among sectors, regions, and with other countries - and for identifying trends that may require policy attention and generate research needs. NCSES also provides extensive tabulations and microdata files for in-depth analysis. Capturing Change in Science, Technology, and Innovation assesses and provides recommendations regarding the need for revised, refocused, and newly developed indicators of STI activities that would enable NCSES to respond to changing policy concerns. This report also identifies and assesses both existing and potential data resources and tools that NCSES could exploit to further develop its indicators program. Finally, the report considers strategic pathways for NCSES to move forward with an improved STI indicators program. The recommendations offered in Capturing Change in Science, Technology, and Innovation are intended to serve as the basis for a strategic program of work that will enhance NCSES's ability to produce indicators that capture change in science, technology, and innovation to inform policy and optimally meet the needs of its user community.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology; Surveys and Statistics

Development Planning: A Strategic Approach to Future Air Force Capabilities - National Research Council (The National Academies Press, 2014)
The development and application of technology has been an essential part of U.S. airpower, leading to a century of air supremacy. But that developmental path has rarely been straight, and it has never been smooth. Only the extraordinary efforts of exceptional leadership - in the Air Forces and the wider Department of Defense, in science and in industry - have made the triumphs of military airpower possible. Development Planning provides recommendations to improve development planning for near-term acquisition projects, concepts not quite ready for acquisition, corporate strategic plans, and training of acquisition personnel. This report reviews past uses of development planning by the Air Force, and offers an organizational construct that will help the Air Force across its core functions. Developmental planning, used properly by experienced practitioners, can provide the Air Force leadership with a tool to answer the critical question, Over the next 20 years in 5-year increments, what capability gaps will the Air Force have that must be filled? Development planning will also provide for development of the workforce skills needed to think strategically and to defectively define and close the capability gap. This report describes what development planning could be and should be for the Air Force.
Keywords: Conflict and Security Issues

Sustainability Strategies Addressing Supply-Chain Air Emissions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Freight Research Program (NCFRP) Report 28: Sustainability Strategies Addressing Supply-Chain Air Emissions identifies potential strategies for accelerating environmental improvement, enhancing performance, and promoting social responsibility of supply chains.The report is intended to help improve decision makers’ understanding of the impact of environmental policies and regulations on the supply chain, focusing on the interrelationships between economic drivers, air quality, and greenhouse gas policy and regulations.
Keywords: Transportation and Infrastructure

Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 - Institute of Medicine (The National Academies Press, 2014)
Determinants of health - like physical activity levels and living conditions - have traditionally been the concern of public health and have not been linked closely to clinical practice. However, if standardized social and behavioral data can be incorporated into patient electronic health records (EHRs), those data can provide crucial information about factors that influence health and the effectiveness of treatment. Such information is useful for diagnosis, treatment choices, policy, health care system design, and innovations to improve health outcomes and reduce health care costs. Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 identifies domains and measures that capture the social determinants of health to inform the development of recommendations for the meaningful use of EHRs. This report is the second part of a two-part study. The Phase 1 report identified 17 domains for inclusion in EHRs. This report pinpoints 12 measures related to 11 of the initial domains and considers the implications of incorporating them into all EHRs. This book includes three chapters from the Phase 1 report in addition to the new Phase 2 material. Standardized use of EHRs that include social and behavioral domains could provide better patient care, improve population health, and enable more informative research. The recommendations of Capturing Social and Behavioral Domains and Measures in Electronic Health Records: Phase 2 will provide valuable information on which to base problem identification, clinical diagnoses, patient treatment, outcomes assessment, and population health measurement.
Keywords: Health and Medicine

Sports-Related Concussions in Youth: Improving the Science, Changing the Culture - Institute of Medicine; National Research Council (The National Academies Press, 2014)
In the past decade, few subjects at the intersection of medicine and sports have generated as much public interest as sports-related concussions - especially among youth. Despite growing awareness of sports-related concussions and campaigns to educate athletes, coaches, physicians, and parents of young athletes about concussion recognition and management, confusion and controversy persist in many areas. Currently, diagnosis is based primarily on the symptoms reported by the individual rather than on objective diagnostic markers, and there is little empirical evidence for the optimal degree and duration of physical rest needed to promote recovery or the best timing and approach for returning to full physical activity. Sports-Related Concussions in Youth: Improving the Science, Changing the Culture reviews the science of sports-related concussions in youth from elementary school through young adulthood, as well as in military personnel and their dependents. This report recommends actions that can be taken by a range of audiences - including research funding agencies, legislatures, state and school superintendents and athletic directors, military organizations, and equipment manufacturers, as well as youth who participate in sports and their parents - to improve what is known about concussions and to reduce their occurrence. Sports-Related Concussions in Youth finds that while some studies provide useful information, much remains unknown about the extent of concussions in youth; how to diagnose, manage, and prevent concussions; and the short- and long-term consequences of concussions as well as repetitive head impacts that do not result in concussion symptoms. The culture of sports negatively influences athletes' self-reporting of concussion symptoms and their adherence to return-to-play guidance. Athletes, their teammates, and, in some cases, coaches and parents may not fully appreciate the health threats posed by concussions. Similarly, military recruits are immersed in a culture that includes devotion to duty and service before self, and the critical nature of concussions may often go unheeded. According to Sports-Related Concussions in Youth, if the youth sports community can adopt the belief that concussions are serious injuries and emphasize care for players with concussions until they are fully recovered, then the culture in which these athletes perform and compete will become much safer. Improving understanding of the extent, causes, effects, and prevention of sports-related concussions is vitally important for the health and well-being of youth athletes. The findings and recommendations in this report set a direction for research to reach this goal.
Keywords: Health and Medicine

Culture Matters: International Research Collaboration in a Changing World: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2014)
In an increasingly interconnected world, science and technology research often transects international boundaries and involves researchers from multiple nations. This paradigm provides both new opportunities and new challenges. As science and technology capabilities grow around the world, United States-based organizations are finding that international collaborations and partnerships provide unique opportunities to enhance research and training. At the same time, enhancing international collaboration requires recognition of differences in culture, legitimate national security needs, and critical needs in education and training. Culture Matters is the summary of a workshop convened by the Government-University-Industry Research Roundtable (GUIRR) in July 2013 to address how culture and cultural perception influence and impact the process by which research agreements are made and negotiated across international boundaries. In this workshop, "Culture Matters: An Approach to International Research Agreements", representatives from around the world and from GUIRR's three constituent sectors - government, university, and industry - gathered to provide input into four specific meeting tracks or domains. The tracks focused on research and agreements affecting or involving people/human subjects; environmental and natural resources; science, engineering, and manufacturing; and agriculture and animal issues. This report examines each of these domains and the role that culture and cultural expectations may have in the forging and implementation of international research agreements.
Keywords: Policy for Science and Technology

Safe Science: Promoting a Culture of Safety in Academic Chemical Research - National Research Council (The National Academies Press, 2014)
Recent serious and sometimes fatal accidents in chemical research laboratories at United States universities have driven government agencies, professional societies, industries, and universities themselves to examine the culture of safety in research laboratories. These incidents have triggered a broader discussion of how serious incidents can be prevented in the future and how best to train researchers and emergency personnel to respond appropriately when incidents do occur. As the priority placed on safety increases, many institutions have expressed a desire to go beyond simple compliance with regulations to work toward fostering a strong, positive safety culture: affirming a constant commitment to safety throughout their institutions, while integrating safety as an essential element in the daily work of laboratory researchers. Safe Science takes on this challenge. This report examines the culture of safety in research institutions and makes recommendations for university leadership, laboratory researchers, and environmental health and safety professionals to support safety as a core value of their institutions. The report discusses ways to fulfill that commitment through prioritizing funding for safety equipment and training, as well as making safety an ongoing operational priority. A strong, positive safety culture arises not because of a set of rules but because of a constant commitment to safety throughout an organization. Such a culture supports the free exchange of safety information, emphasizes learning and improvement, and assigns greater importance to solving problems than to placing blame. High importance is assigned to safety at all times, not just when it is convenient or does not threaten personal or institutional productivity goals. Safe Science will be a guide to make the changes needed at all levels to protect students, researchers, and staff.
Keywords: Math, Chemistry, and Physics; Policy for Science and Technology; Conflict and Security Issues

The Federal Aviation Administration’s Approach for Determining Future Air Traffic Controller Staffing Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB has released the final version of Special Report 314: The Federal Aviation Administration’s Approach for Determining Future Air Traffic Controller Staffing Needs that examines the methods used by the Federal Aviation Administration (FAA) to estimate how many controllers are needed to staff its air traffic control facilities and its processes for using these estimates to properly distribute controllers across facilities.According to the report, the FAA’s models for determining air traffic controller staffing needs are suitable for developing initial estimates of the number of controllers required at terminal areas and airport towers, but the models used for the centers controlling aircraft en route between airports can be improved. In addition, as a matter of priority, the FAA should collaborate with the National Air Traffic Controllers Association to develop and implement an enhanced tool for all facilities that is capable of creating efficient controller work schedules that incorporate fatigue mitigation strategies.The report recommends that the FAA analyze a wide range of data, such as accident and incident reports and voluntary reports by controllers, to identify relationships between staffing and safety. In addition, the controller workforce should be involved in staffing decisions, particularly as knowledge emerges about relevant safety issues. The FAA also should ensure that staffing continues to be appropriate as it implements the new air traffic operations environment associated with the Next Generation Transportation System, a modernization initiative to shift air traffic management from ground-based radar to a satellite system, the report says.A press release on the report is available for download.A report summary has been published in TR News 297.
Keywords: Transportation and Infrastructure

Guide to Accelerating New Technology Adoption through Directed Technology Transfer - Transportation Research Board (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 768: Guide to Accelerating New Technology Adoption through Directed Technology Transfer presents a framework and guidance on how to use technology transfer to accelerate innovation within a state department of transportation or other such agency.
Keywords: Transportation and Infrastructure

U.S. Air Force Strategic Deterrence Analytic Capabilities: An Assessment of Tools, Methods, and Approaches for the 21st Century Security Environment - National Research Council (The National Academies Press, 2014)
Since the early 1960s, the U.S. strategic nuclear posture has been composed of a triad of nuclear-certified long-range bombers, intercontinental ballistic missiles, and submarine-launched ballistic missiles. Since the early 1970s, U.S. nuclear forces have been subject to strategic arms control agreements. The large numbers and diversified nature of the U.S. nonstrategic (tactical) nuclear forces, which cannot be ignored as part of the overall nuclear deterrent, have decreased substantially since the Cold War. While there is domestic consensus today on the need to maintain an effective deterrent, there is no consensus on precisely what that requires, especially in a changing geopolitical environment and with continued reductions in nuclear arms. This places a premium on having the best possible analytic tools, methods, and approaches for understanding how nuclear deterrence and assurance work, how they might fail, and how failure can be averted by U.S. nuclear forces. U.S. Air Force Strategic Deterrence Analytic Capabilities identifies the broad analytic issues and factors that must be considered in seeking nuclear deterrence of adversaries and assurance of allies in the 21st century. This report describes and assesses tools, methods - including behavioral science-based methods - and approaches for improving the understanding of how nuclear deterrence and assurance work or may fail in the 21st century and the extent to which such failures might be averted or mitigated by the proper choice of nuclear systems, technological capabilities, postures, and concepts of operation of American nuclear forces. The report recommends criteria and a framework for validating the tools, methods, and approaches and for identifying those most promising for Air Force usage.
Keywords: Conflict and Security Issues

Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 20: Estimating the Economic Impact of Air Cargo Operations at Airports, Part 1: User’s Guidebook and Part 2: Research Report provides guidance and tools to practitioners who estimate the economic value of air cargo facilities and operations to their communities and regions.
Keywords: Transportation and Infrastructure

Interim Report of a Review of the Next Generation Air Transportation System Enterprise Architecture, Software, Safety, and Human Factors - National Research Council (The National Academies Press, 2014)
The Next Generation Air Transportation System (NextGen) is an effort begun in 2003 whose goals include improving the capacity, efficiency, and safety of the U.S. air transportation system and also enabling reduction in noise, pollution, and energy use. The Federal Aviation Administration and various stakeholders, including equipment providers, airlines, and contractors, are currently implementing both near-term and midterm capabilities of this effort. Interim Report of a Review of the Next Generation Air Transportation System Enterprise Architecture, Software, Safety, and Human Factors is part of a larger project to examine NextGen's enterprise architecture and related issues. This interim report provides an initial assessment focusing on challenges of system architecture for software-intensive systems.
Keywords: Computers and Information Technology; Engineering and Technology

Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020: Interim Report - National Research Council (The National Academies Press, 2014)
Advanced computing capabilities are used to tackle a rapidly growing range of challenging science and engineering problems, many of which are compute- and data-intensive as well. Demand for advanced computing has been growing for all types and capabilities of systems, from large numbers of single commodity nodes to jobs requiring thousands of cores; for systems with fast interconnects; for systems with excellent data handling and management; and for an increasingly diverse set of applications that includes data analytics as well as modeling and simulation. Since the advent of its supercomputing centers, the National Science Foundation (NSF) has provided its researchers with state-of-the-art computing systems. The growth of new models of computing, including cloud computing and publically available by privately held data repositories, opens up new possibilities for NSF. In order to better understand the expanding and diverse requirements of the science and engineering community and the importance of a new broader range of advanced computing infrastructure, the NSF requested that the National Research Council carry out a study examining anticipated priorities and associated tradeoffs for advanced computing. This interim report identifies key issues and discusses potential options. Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020 examines priorities and associated tradeoffs for advanced computing in support of NSF-sponsored science and engineering research. This report is an initial compilation of issues to be considered as future NSF strategy, budgets, and programs for advanced computing are developed. Included in the report are questions on which the authoring committee invites comment. We invite your feedback on this report, and more generally, your comments on the future of advanced computing at NSF.
Keywords: Computers and Information Technology

Using the Economic Value Created by Transportation to Fund Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 459: Using the Economic Value Created by Transportation to Fund Transportation presents information on financing mechanisms used by transportation agencies to capture a portion of the economic value created by public investment in transportation infrastructure to fund transportation improvements.The report provides an overview of ten types of “value capture” mechanisms and presents case examples of how transportation agencies have used these mechanisms to help fund specific highway projects.
Keywords: Transportation and Infrastructure

Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management - National Research Council (The National Academies Press, 2014)
The United States military is arguably the most intensely technological, complex enterprise in existence. When compared to the gross domestic products of other countries, the Department of Defense (DoD) budget ranks above all but about 20 nations. If viewed as a company, it would be the largest globally with the most employees. Major investments in weapons systems using advanced technologies provide an advantage over competing systems. Each weapon, platform, vehicle, and person in an operating force is a node in one or more advanced networks that provide the ability to rapidly form a coherent force from a large number of broadly distributed elements. DoD's ability to create and operate forces of this nature demands a competent understanding by its workforce of the composition, acquisition, and employment of its technology-enabled forces. Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management focuses on the graduate science, technology, engineering, mathematics and management (STEM+M) education issues of the Air Force, Navy, and Marines. This report assesses the cost, benefits, and organizational placement of DoD institutions that grant degrees in STEM+M and evaluates alternative ways - for example, civilian institutions and distance learning - to ensure adequate numbers and high-quality education outcomes for DoD personnel.
Keywords: Education

Health Impact Assessment of Shale Gas Extraction: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Natural gas extraction from shale formations, which includes hydraulic fracturing, is increasingly in the news as the use of extraction technologies has expanded, rural communities have been transformed seemingly overnight, public awareness has increased, and regulations have been developed. The governmental public health system, which retains primary responsibility for health, was not an early participant in discussions about shale gas extraction; thus public health is lacking critical information about environmental health impacts of these technologies and is limited in its ability to address concerns raised by regulators at the federal and state levels, communities, and workers employed in the shale gas extraction industry. Health Impact Assessment of Shale Gas Extraction is the summary of a workshop convened in 2012 by the Institute of Medicine (IOM) Roundtable on Environmental Health Sciences, Research, and Medicine to discuss the human health impact of shale gas extraction through the lens of a health impact assessment. Eminent scientists, physicians, public health experts, and representatives from government agencies at federal and state levels, from nongovernment organizations, from the business sector, and from interest groups representing the interests of the citizens met to exchange ideas and to inform on hydraulic fracturing as a means of extraction of natural gas. This report examines the state of the science regarding shale gas extraction, the direct and indirect environmental health impacts of shale gas extraction, and the use of health impact assessment as a tool that can help decision makers identify the public health consequences of shale gas extraction.
Keywords: Health and Medicine

The Nexus of Biofuels, Climate Change, and Human Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Liquid fuels are a major part of modern life. They supply energy for ground, water, and air transportation as well as power for industrial and farming machinery. But fossil fuels - the dominant liquid fuel in use for well over a century - have many disadvantages. The use of fossil fuels has obvious health downsides, such as emissions of pollutants that are directly harmful to health. The burning of fossil fuels produces greenhouse gases, which contribute to global warming, itself a long-term threat to human health. There have also been health concerns related to insecurity of liquid fuel supplies and the potential of international conflicts being caused by fuel scarcity. Furthermore, there are concerns that the world's large but still limited supply of fossil fuels could be strained by the increasing demand that results from societies around the world achieving greater prosperity. In the face of these concerns, new policies have been created that encourage the development of renewable sources of energy in general and biofuels in particular. In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2- day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source.
Keywords: Health and Medicine

Big Data in Materials Research and Development: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
Big Data in Materials Research and Development is the summary of a workshop convened by the National Research Council Standing Committee on Defense Materials Manufacturing and Infrastructure in February 2014 to discuss the impact of big data on materials and manufacturing. The materials science community would benefit from appropriate access to data and metadata for materials development, processing, application development, and application life cycles. Currently, that access does not appear to be sufficiently widespread, and many workshop participants captured the constraints and identified potential improvements to enable broader access to materials and manufacturing data and metadata. This report discusses issues in defense materials, manufacturing and infrastructure, including data ownership and access; collaboration and exploitation of big data's capabilities; and maintenance of data.
Keywords: Engineering and Technology